Raccontare la geologia attraverso le story-telling Roma dal 1820 al 2008 (GEOmedia, 2016)
PAROLE CHIAVECartografia geologica; Storia della geologia; Geologiaurbana; RomaABSTRACTGeological mapping is one of the most innovative "discoveries" (inEarth Sciences development) of the 19th century and it representedthe basic knowledge for the economic exploitation of many Europeancountries. In 1873, with the foundation of the Regio Ufficio Geologico,started the systematic geological survey of the Italian territory andits cartographic representation. In the previous period some scientistsreported on scientific publications the results of their studies and surveyscarried out in different parts of the peninsula. Undoubtedly, theearly example is the "Geological scheme of Rome”, realized by GiovanniBattista Brocchi between 1820 and 1830. The analysis of scientificand cartographic production carried out by several authors in theurban area of Rome and its surroundings permitted us to built a Storytelling project finalized to highlight the progress of geological knowledge,placing the individual works in the historical and cultural contextof the period. This reconstruction path is done by exploiting the potentialof ESRI ArcGIS Online tools, with the purpose of enhancing thescientific and cultural content of the geological cartography contributingto the knowledge of Geological Sciences development.